2019
DOI: 10.1053/j.jfas.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Nonanimal Hyaluronic Acid for the Treatment of Ankle Osteoarthritis: AProspective, Single-Arm Cohort Study

Abstract: Ankle osteoarthritis (OA) can cause disabling symptoms, and some patients prefer to be treated with minimally invasive procedures. Nonanimal hyaluronic acid (NASHA) is a cross-linked hyaluronic acid product that has a prolonged intra-articular residence time. The authors report the first study of NASHA for the treatment of ankle OA. Thirtyseven patients with Kellgren-Lawrence grade II or III ankle OA received an intra-articular injection of NASHA (1 mL). Outcomes included visual analogue scale (VAS) scores for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
4
0
2
Order By: Relevance
“…Currently, there are a total of 18 studies assessing the effectiveness of IA injections of HA in the treatment ankle OA, seven RCTs, nine case series, and two prospective cohort studies [73,78]. Each case series and the two prospective cohort studies concluded that intra articular HA was an effective and tolerable in the treatment of osteoarthritic ankle pain, with some studies noting pain relief for up to 12--18 months following injection [73,78]. All seven RCTs concluded that intra-articular HA injections lead to significant relief of ankle pain.…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…Currently, there are a total of 18 studies assessing the effectiveness of IA injections of HA in the treatment ankle OA, seven RCTs, nine case series, and two prospective cohort studies [73,78]. Each case series and the two prospective cohort studies concluded that intra articular HA was an effective and tolerable in the treatment of osteoarthritic ankle pain, with some studies noting pain relief for up to 12--18 months following injection [73,78]. All seven RCTs concluded that intra-articular HA injections lead to significant relief of ankle pain.…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…Серед загальних побічних явищ після введення ГК описують головний біль, артралгію, назофарингіт тощо [31].…”
Section: результатиunclassified
“…[ 98 ] Nevertheless, despite the considerable interest in these products, many studies in the clinical stage also combine this with other drugs such as dexamethasone, hexacetonide, mannitol, and botulin toxin, among others, as well as the use of other innovative products that are described in Table 2. [ 96–106 ]…”
Section: Translation To the Clinicmentioning
confidence: 99%
“…[98] Nevertheless, despite the considerable interest in these products, many studies in the clinical stage also combine this with other drugs such as dexamethasone, hexacetonide, mannitol, and botulin toxin, among others, as well as the use of other innovative products that are described in Table 2. [96][97][98][99][100][101][102][103][104][105][106] When a team takes their product into clinical trials, there are unavoidable safety concerns and issues to consider. These are first 1) transversal to all clinical products and then 2) those associated with the product itself have to be weighed.…”
Section: Translation To the Clinicmentioning
confidence: 99%